PROTOCOL: The impact of infrastructure on low‐income consumers' nutritious diet, women's economic empowerment, and gender equality in low‐ and middle‐income countries: An evidence and gap map - Obeng‐Amoako, G.A.O.; Nyan, C.P.; Okyere, C.Y.; et al. (Campbell Systematic Reviews, 2023)
This is the protocol for an evidence and gap map. The objectives are as follows: this evidence and gap map (EGM) aims to identify, map, and provide an overview of the existing evidence and gaps on the impact of different types of physical infrastructure on various outcomes of low‐income consumers' nutritious diet, women's economic empowerment, and gender equality in low‐ and middle‐income countries. The specific objectives of the EGM are: (1) identify clusters of evidence that offer opportunities for evidence synthesis and (2) identify gaps in evidence where new studies, research, and evaluations are needed
Research Article
Keywords: protocol; evidence and gap map; various outcomes of low‐income consumers' nutritious diet